MATHEMATICAL MODELING OF CHEMICAL-TECHNOLOGICAL PROCESSES, INFORMATION PROCESSING (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The article provides scientific and theoretical information on mathematical modeling of chemical-technological processes, data processing.